The Effect of Chitosan on Lipid Profile of Sprague Dawley Rat Blood Serum - Martati, Erryana; Lestari, Lily Arsanti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
Chitosan shares characteristic with dietary fiber which can interact with lipids and/or cholesterol in the intestinal lumen, consequently, reduce their absorption. The effect of chitosan concentration on the serum cholesterol levels (total cholesterol, HDL, LDL cholesterol and trigliceride) and digesta profile of Sprague Dawley rats were investigated. A two month old Sprague Dawley rats consisted of six groups with seven animals of each group were adapted for one week by giving standard diet (AIN-93). Then they were treated with hypercholesterol diet containing approximately 200 mg/kg cholesterol for one week. At the end of this week, cholesterol level was measured. The parameter for hypercholesterolemic rats was the raising level of serum cholesterol as much as 130 mg/dl. The first three groups of rats were treated with standard diet (AIN-93) with 0%, 2.5%, and 5% of chitosan. The second three groups were treated with hypercholesterol diet with the same treatments as the first one. Blood was drawn from eyes (reorbital plexus) every week for analyzing cholesterol levels (total cholesterol, HDL, LDL cholesterol and triglicerides). At the end of the treatment, seven rats were killed after one day fasting then liver and caecum were collected for analyzing.Research showed that chitosan of 2.5% and 5% in the diet did not alter body and liver weight of the group with standard diet (AIN-93) treatment. Conversely, body wieght decreased and liver weight increased in the hypercholesterol diet treatments. Chitosan also increased digesta weight and cholesterol level either in standard or hypercholesterol diet treatments. Serum profiles showed that chitosan treatment of 2.5% or 5% decreased total cholesterol, LDL cholesterol and triglyceride but increased HDL cholesterol.Keyword: lipid profile, blood serum, chitosan, hypercholesterol